Psychometric properties of the Psychopathy Checklist : Youth version among portuguese juvenile delinquents - Pechorro, Pedro Fernandes dos Santos (2016)
The main aim of the present study was to examine some psychometric properties of the Psychopathy Checklist: Youth Version (PCL:YV) among Portuguese juvenile delinquents. With forensic sample of 192 incarcerated male participants, the Portuguese version of the PCL:YV demonstrated promising psychometric properties of the three-factor model of youth psychopathy, internal consistency, convergent validity, concurrent validity, and retrospective validity that generally justify its use among Portuguese youths. Statistically significant associations were found with age of criminal onset, frequency of crimes, number of victims, and use of physical violence.